Shallot (Allium cepa L.) Skin Ethanol Extract Neutralizes Liver Oxidative Stress in Diazinon-Induced Wistar Rats - Shahifa Audy Rahima; Rosita Dewi; Nindya Shinta Rumastika; Dina Helianti (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
ABSTRACTDiazinon has a hepatotoxic effect since it is metabolized in the liver involving Kupffer cells (KCs) activation, increasing reactive oxygen species (ROS). The flavonoids contained in shallot (Allium cepa L.) skin act as antioxidants neutralizing oxidative stress. This study aims to determine the effect of shallot skin ethanol extract (SSEE) on liver MDA level and activated KCs histopathology. The total flavonoids level of SSEE was measured using the aluminum chloride colorimetric method and resulted in 228.1 mg QE/g. Rats were divided into normal, diazinon, and SSEE groups. Diazinon was administered at a dose of 40 mg/kg b.w. for 7 days, followed by SSEE at the dose of 600, 900, and 1,200 mg/kg b.w. for 7 days. Liver malondialdehyde (MDA) level was measured using the MDA-TBA method. The results revealed that diazinon increased liver MDA level (p <0.05), while SSEE at doses of 900 and 1,200 mg/kg b.w. decreased liver MDA level equal to normal (p>0.05). Activated KCs in the SSEE group at a dose of 1,200 mg/kg b.w. was impressively equal to the normal group. In conclusion, SSEE at dose of 1,200 mg/kg b.w. neutralize liver oxidative stress due to diazinon indicated by the decrease of liver MDA level and activated KCs equal to normal.Keywords: antioxidant, diazinon, Kupffer cell, liver, MDA, shallotCorrespondence: rosita.fk@unej.ac.id